Pengaruh Return on Asset dan Biaya Lingkungan terhadap Nilai Perusahaan pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia - Fitria, Safira Nur; Lestari, Dwi Indah (Transpublika Publisher, 2025)
The mining sector is one of the largest contributors to state revenue in Indonesia, with revenues reaching IDR 124.4 trillion in 2021. However, the sector faces challenges related to fluctuations in company value and demands for environmental responsibility. The main goal of this research is to explore how the costs related to the environment and Return on Assets (ROA) affect the valuation of publicly traded mining companies on the Indonesia Stock Exchange. Specifically, the study will look at mining companies that have remained on the IDX between the years 2020 and 2023 and have included their environmental expenses in their sustainability reporting. Out of a total of 186 mining firms, only 8 were selected for analysis using a targeted sampling method. The results of the study suggest that environmental costs play a crucial role in determining a company's worth, whereas the Return on Assets does not significantly impact the overall value of the firm. This finding implies that investors need to consider other factors in making investment decisions in the mining sector.